Associations of Tobacco Advertising Appeal With Intentions to Use Alternative Tobacco Products Among Young Tobacco Users Experiencing Homelessness. Issue 2 (February 2020) - Shadel, William G.; Tucker, Joan S.; Seelam, Rachana; Golinelli, Daniela; Siconolfi, Daniel
Purpose: Virtually nothing is known about the potential effects of tobacco advertising on tobacco use among youth experiencing homelessness, a vulnerable population with high tobacco use rates. This study examines associations between the appeal of advertising for 5 classes of tobacco product (electronic cigarettes, hookah, cigars, cigarillos, and smokeless tobacco) and future intentions to use those products again among homeless youth who had indicated any level of lifetime use. Design: A cross-sectional design was used. Setting: Settings were 25 service and street sites in Los Angeles County. Participants: A probability sample of 469 young tobacco users experiencing homelessness (mean age = 22; 71% male; 29% non-Hispanic White) was recruited. Measures: Assessments included product-specific tobacco advertising appeal and future intentions to use the product again, as well as a range of covariate controls (eg, demographics, homelessness severity, current tobacco use, general advertising exposure). Analysis: Linear regression tested for associations between the appeal of advertising for a specific tobacco product and intentions to use that product again in the future, controlling for myriad covariates. Results: Advertising appeal was positively associated with future intentions to use again for electronic cigarettes ( P = .006) and hookah ( P = .001), but not cigars ( P = .486), cigarillos ( P = .126), or smokeless tobacco ( P = .109). Conclusion: Results suggest that advertising appeal may increase use of certain tobacco products among youth experiencing homelessness. However, differences in themes emphasized by advertising for specific tobacco products could differentially influence use in this population.